2013
DOI: 10.1016/j.polymer.2013.05.025
|View full text |Cite
|
Sign up to set email alerts
|

Influence of rheology and morphology on foaming of PS-b-PMMA diblock copolymers and their composites with modified silica nanoparticles

Abstract: In this study, the influence of rheological and morphological properties on the foaming behaviour of polystyrene-block-poly(methyl methacrylate) (PS-b-PMMA) diblock copolymers and their composites with PMMA modified silica nanoparticles is discussed. The blowing agent was carbon dioxide. Cylindrical and lamellar types of PS-b-PMMA diblock copolymers with different molecular weights were chosen in order to elucidate the influence of morphology and molecular weight on the foaming behaviour. The microphase-separa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 52 publications
1
11
0
Order By: Relevance
“…Recently, Handge et al have reported a similar phenomenon; that is, the TTS principle was not well obeyed in the modulus curves for PS-b-PMMA diblock copolymers with a lamellar morphology, but the samples with cylindrical morphology obeyed the TTS principle. 4 As we know, both T g s of PS and PMMA are very close in PS-b-PMMA diblock copolymers, 4 and the T g of PS is much higher than that of PE in this work. So it is difficult to explain that the applicability of TTS for the copolymers with microphaseseparated structure results from that the relaxation time scales of two phases are very similar due to small difference in both T g s. 16 We think that the volume fraction of the backbone phase for the PSVS52.7-3.5-PE4.9 and PSVS54.4-2.7-PE10.7 is comparatively high (24% and 35%), which more easily result in more than one relaxation properties, leading to the failure of the TTS principle.…”
Section: Macromoleculessupporting
confidence: 48%
“…Recently, Handge et al have reported a similar phenomenon; that is, the TTS principle was not well obeyed in the modulus curves for PS-b-PMMA diblock copolymers with a lamellar morphology, but the samples with cylindrical morphology obeyed the TTS principle. 4 As we know, both T g s of PS and PMMA are very close in PS-b-PMMA diblock copolymers, 4 and the T g of PS is much higher than that of PE in this work. So it is difficult to explain that the applicability of TTS for the copolymers with microphaseseparated structure results from that the relaxation time scales of two phases are very similar due to small difference in both T g s. 16 We think that the volume fraction of the backbone phase for the PSVS52.7-3.5-PE4.9 and PSVS54.4-2.7-PE10.7 is comparatively high (24% and 35%), which more easily result in more than one relaxation properties, leading to the failure of the TTS principle.…”
Section: Macromoleculessupporting
confidence: 48%
“…The covalent bonding of different types of monomers in block copolymers allows for combining different properties, e.g., for enhancing the toughness of polymers by incorporation of a soft block or for the compatibilisation of polymer blends [10][11][12][13]. In addition, the phenomenon of microphase separation enables the design of an isoporous active layer in membranes [14] and the preparation of structured cell walls in polymer foams [15]. The effect of block copolymer micelles on nucleation of foam cells in thermoplastic polymers was also explored [16].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the influence of molecular parameters (e.g., molecular weight) on the foam properties needs to be investigated further. So far, the influence of the morphology and molecular architecture of block copolymers on the viscoelastic properties has been investigated by several groups on systems such as polystyrene-block-poly(methyl methacrylate), polystyrene-block-polyisoprene or polystyrene-block-polyisoprene-block-polystyrene block copolymers [15,49,50].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, block copolymers are widely used as additives in plastic technology [7,16], since they have unique properties, which result from their ability to self-assemble into different microphase morphologies [1,2,17]. Various works were accomplished with the focus on the analysis of rheological and dielectric properties of block copolymers as well as on relations between morphology and molecular architecture [18][19][20]. The phenomenon of microphase separation depends on many factors, such as the chemical type of the monomers that a specific block copolymer consists of, the relative amounts of the different blocks, the degree of polymerization, and the temperature.…”
Section: Introductionmentioning
confidence: 99%